Markov chains for the identification of areas at higher risk of earthquake occurrence in Lima-Ica 2019 - Risco Franco, Carlos (2019)
In this study, the Markov Chains model was applied to identify areas with the highest risk of earthquakes in the geographic area of Lima - Ica, which is considered one of the most active seismic zones in Peru. There are few research works with the application of probabilistic models to earthquakes in Peru. In the present study we have used the information of the earthquakes that have occurred in Lima-Ica from 2017 to 2019 (IGP) and we have found that the Lima-Oeste area is the one with the highest risk of earthquakes, approaching this result , for the case of Lima, with the result found by other authors, with different methods.